Field-scale screening of pumpkin cultivars for cost-effectiveness of “repairing while producing” in cadmium-arsenic co-contaminated agricultural land - Xingxiu Huang; Qingzhou Yu; Mengya Zhou; Chongjian Ma; Huashou Li (Food Chemistry: X)
Soil contamination with heavy metals poses a significant health risk as these metals can be transferred to humans through agricultural products. This study aimed to identify pumpkin varieties with low cadmium and arsenic accumulation. To this end, we evaluated 25 pumpkin varieties. Results indicated that the accumulated contents of heavy metals in each organ followed the order: root (0.148 mg·kg−1) > leaf (0.100 mg·kg−1) > stem (0.076 mg·kg−1).The transfer coefficients of these 25 pumpkin varieties were greater for leaves than for stems, yet none exceeded 1. Rhizosphere pH is a critical factor influencing the uptake of Cd by pumpkins, with a less significant impact on As uptake. This study provides a foundation for identifying pumpkin varieties with low Cd and As accumulation potential.Additionally, it contributes to the exploration of pumpkin's potential as a phytoremediation resource and its safe production and utilization in heavy metal-contaminated soils.